(untitled) (Research, Society and Development, 2021)
Introduction: The nurse is important for a humanized care in risk classification, including the identification and management of patients with suspected or confirmed COVID-19. Objective: to report the experience of a nurse in risk classification during the COVID-19 pandemic period. Method: This is an experience report carried out in an emergency care unit in Fortaleza, Ceará, from March 2020 to April 2021. Minayo’s thematic analysis was used to define thematic categories. Results: The emerging categories were: patient risk classification with COVID-19 and definition of care flows. In this context, the nurse appears as a priority-setter according to pathological criteria related to vital signs and general status, determining categories of care: little urgent, urgent or emergency. In addition, it observes criteria that contribute to the flow of care according to the degree of care for the disease: mild, moderate or severe, being time-dependent elements. Final considerations: The nurse is a key element in the identification of severities related to COVID-19, contributing to the definition of flows and subsequent patient care.